Systematic analysis of gout burden among young adults in China from 1990 to 2021: findings from the global burden of disease study 2021 - Zhong, Yuxin; Li, Yan; Hu, Chenyu; Tao, Tao; Hao, Liyuan; Li, Na; Zeng, Xiaoyan; Zhang, Zixin; Hu, Xiaoyu (Frontiers in Public Health, 2025)
BackgroundGout, a disabling inflammatory arthritis, closely linked to metabolic diseases such as hyperuricemia, obesity, hypertension, and diabetes, is increasingly prevalent among young adults in China. Understanding the burden of gout and its risk factors among young adults in China is crucial for developing effective prevention and management strategies.MethodsWe analyzed data from the Global Burden of Disease Study 2021 (GBD 2021) on gout prevalence, incidence, and disability-adjusted life years (DALYs) among young adults (individuals aged 15–39 years) in China from 1990 to 2021. Joinpoint regression and the AutoRegressive Integrated Moving Average (ARIMA) model were used to assess trends and predict future burden. Summary exposure values (SEVs) were used to evaluate risk factors.ResultsThe study found that the burden of gout among young adults in China is significantly higher than the global average and shows a continuous upward trend. Males have a higher burden and age-standardized rates on all indicators, including prevalence, incidence, and DALYs. Joinpoint regression analysis revealed that from 1990 to 2021, the burden of gout has experienced rapid growth, stabilization, and a resurgence of acceleration since 2019. ARIMA model projects different epidemiological trends for gout across 2022–2036, with age-standardized prevalence rate (ASPR) and age-standardized incidence rate (ASIR) declining while age-standardized DALYs rate (ASDR) gradually rise. Gender-specific disparities persist. Females demonstrate a predictable rise in ASPR, ASIR and ASDR. Despite males facing higher baseline burdens and accelerating ASDR growth, their ASPR and ASIR exhibit downward trends. A significant rise in gout risk factors among Chinese aged 15–39 from 1990 to 2021 highlights the need to face the upcoming gout burden and carry out targeted measures for this population.ConclusionThe rising burden of gout among young Chinese adults demands immediate gender- and age-specific public health action. Targeted interventions focusing on modifiable risk factors such as dietary habits and lifestyle are crucial to reduce the impact of gout on young adults.